Genetic analysis and screening of detoxification-related genes in an amitraz-resistant strain of Panonychus citri. Issue 6 (18th December 2020) - Yu, Shi-Jiang; Cong, Lin; Liu, Hao-Qiang; Ran, Chun
Abstract: Panonychus citri (McGregor) is the most common pest in citrus-producing regions. Special low-toxicity acaricides, such as spirocyclic tetronic acids and mite growth inhibitors, have been used for a long time in China. However, pesticide resistance in mites is a growing problem due to the lack of new acaricide development. Wide-spectrum insecticides, such as amitraz have gained acceptance among fruit growers. An amitraz-resistant strain of P. citri was obtained by indoor screening to examine field resistance monitoring of mites to acaricides and to explore the resistant mechanism of mites against amitraz. The amitraz-resistant strain of P. citri had an LC50 value of 2361.45 mg l −1 . The resistance ratio was 81.35 times higher in the resistant strain of P. citri compared with the sensitive strain. Crossing experiments between the sensitive and resistant strains of P. citri were conducted, resulting in a D value of 0.11 for F1 SS♀×RS♂ and 0.06 for F1 RS♀×SS♂ . Reciprocal cross experiments showed that the dose–mortality curves for the F1 generations coincided, indicating that the resistance trait was not affected by cytoplasmic inheritance. The dose–expected response relationship was evaluated in the backcross generation and a significant difference was observed compared with the actual value. The above results indicate that the inheritance of resistance trait was incompletely dominant, governed by polygenes on the chromosome. Synergism studies demonstrated that cytochrome P450s and esterase may play important roles in the detoxification of amitraz. Based on differential gene analysis, 23 metabolism-related genes of P. citri were identified, consistent with the results of synergism studies. Real-time PCR verification implied that P450s, ABC transporters, and acetylcholinesterase might influence the detoxification of amitraz by P. citri . These results provide the genetic and molecular foundation for the management of pest mite resistance.